Ultra-Wideband Indoor Channel Modelling Using Ray-Tracing Software for through-the-Wall Imaging Radar. (24th June 2010) - Lièbe, Christophe; Combeau, Pierre; Gaugue, Alain; Pousset, Yannis; Aveneau, Lilian; Vauzelle, Rodolphe; Ogier, Jean-Marc
Abstract : This paper presents a new software for design of through-the-wall imaging radars. The first part describes the evolution of a ray tracing simulator, originally designed for propagation of narrowband signals, and then for ultra-wideband signals. This simulator allows to obtain temporal channel response to a wide-band emitter (3 GHz to 10 GHz). An experimental method is also described to identify the propagation paths. Simulation results are compared to propagation experiments under the same conditions. Different configurations are tested and then discussed. Finally, a configuration of through-the-wall imaging radar is proposed, with different antennas patterns and different targets. Simulated images will be helpful for understanding the experiment obtained images.